Difficulties experienced by endodontics researchers in conducting studies and writing papers - Betul Aycan Alim-Uysal; Selin Goker-Kamali; Ricardo Machado (Restorative Dentistry & Endodontics, 2022)
ObjectivesThe study investigated the difficulties experienced by endodontics researchers around the world in conducting studies and writing papers.Materials and MethodsA survey consisting of 18 questions on the difficulties experienced by endodontics researchers in performing studies and writing papers was e-mailed to academics in the field of endodontics working at 202 universities. The independent risk factors were analyzed using binary logistic regression at a significance level of 0.05.ResultsA total of 581 individuals (10.7%) agreed to participate in the study. Almost half the participants (48.2%) reported that they had received some type of training in conducting studies and writing papers. In response to the question, “Do you get help from a statistician to perform the statistical analyses of your studies?,” 77.1% answered “yes.” Around 40% of the participants stated that the need to obtain ethical approval negatively affected their desire to conduct studies. The participants’ regions had no effect on the reported difficulties associated with writing papers in English or conducting statistical analyses (p > 0.05). Most participants (81.8%) reported difficulties in writing the Discussion section, regardless of their region, academic degrees, or years of experience.ConclusionsThe participants stated they experienced difficulties in many areas, such as conducting statistical analyses, finding new ideas, and writing in English. Engaging in a detailed examination of ethics committee rules, expanding biostatistics education, increasing the number of institutions providing research funding, and increasing the number of endodontics journals can increase the enthusiasm of endodontics researchers to publish papers.